Working memory and multilingualism: balanced language proficiency predicts verbal working memory. Issue 8 (14th September 2022) - Espi-Sanchis, Gabriel; Cockcroft, Kate
ABSTRACT: This study investigated the relationship between balanced multilingualism and working memory. Specifically, it reports on the relationship between balanced proficiency in speaking, reading and comprehension (across three languages), and verbal and visuospatial working memory in young South African adults. Information about participants' language experience and proficiency in up to three languages was used to create variables capturing the extent of balance among languages spoken. Participants also completed a comprehensive working memory test battery (tapping verbal and visuospatial storage and processing). While effect sizes were small across all regressions, balanced proficiency among languages had a significant effect on verbal (but not visuospatial) working memory, after controlling for socioeconomic status. The results suggest that multilingualism may lead to domain-specific working memory advantages when processing verbal content. The absence of any domain-general effects supports the scepticism surrounding a bilingual effect on working memory (and executive function more generally). The implications of these findings for theories of working memory are discussed.